The experience of close personal relationships after stroke: scoping review and thematic analysis of qualitative literature. Issue 3 (2nd December 2022) - Ford, Amy; Douglas, Jacinta; O'Halloran, Robyn
Abstract: Background and Purpose: Psychosocial difficulties, including changed relationships are among the most pervasive and concerning issues following stroke. This study aimed to collate and thematically analyse qualitative literature describing the experience of close personal relationships from the perspective of stroke survivors. Method: Using a scoping review methodology, four databases (CINAHL/EBSCO, MEDLINE/Pubmed, Embase, Psychinfo) were systematically searched, yielding 3100 citations. Following exclusion of duplicates and screening against inclusion criteria at title/abstract and full text levels, 53 articles were included in the review. Data were charted and thematically analysed. Results: While research has increased since 2000, longitudinal designs are few. Four overarching themes and 12 subthemes were identified. 'Social disruption' described changing social worlds, lost social opportunities and shrinking networks. 'Changed relationships' included changed family and spousal relationships and changed parenting relationships. The third theme 'relationships help' highlighted positive aspects including belonging, support and a life worth living. The final theme was 'coping with an altered social world' and described adjustment and emotional responses. Conclusions: Relationships are an important aspect of life post stroke but are subject to changes and challenges. This article brings together a breadth of qualitative data to describe lived experiences. Further research, in particular, longitudinal research is required.